The Effects of P, I and D Parameters in Automatic Liquid Level Control Using UniTrain Module - Alfatirta Mufti (Jurnal Rekayasa Elektrika, 2013)
The research discusses some experiments to control the level of liquid inside a tank by using PID controllers which can be divided into four categories. The experiments describe the effect of P, I, and D element. It also discusses the best possible controller, which is a PI controller, for the liquid level tank system. The liquid level controlling is done by adjusting the voltage pump which will further regulate the flow rate of the fluid entering the inlet valve. The liquid that flows through the outlet valve is considered as the disturbance variable to the system. The liquid tank sensor needs to be calibrated prior to the experiments. Calibration can be done manually by using a digital multimeter or by using the computer sofware that is connected directly to the plant system. Set point and PID parameters are determined by the UniTrain and the computer interface. In these experiments, PI controller has the best result with a medium proportional gain (KP = 5) and a small integral gain (TN = 0.2).